A complete mass balance for plastics in a wastewater treatment plant - Macroplastics contributes more than microplastics. (1st August 2021) - Rasmussen, Lasse Abraham; Iordachescu, Lucian; Tumlin, Susanne; Vollertsen, Jes
Highlights: A complete mass balance for plastics in a wastewater treatment plant was established. Plastics of all sizes down to 10 µm were identified in screening material, influent, digested sludge, and effluent using µFTIR imaging. The removal efficiency was >98.8% for small microplastics <500 µm and were mostly (65.8%) retained in the sludge. For all plastics entering the plant, the removal efficiency was 99.6 % and were largely (73.4%) retained in the screenings. More than five times the mass of plastic found in the sludge were identified in screening materials. Abstract: A complete plastic particle mass balance was established at Sweden's second-largest wastewater treatment plant. It comprised material collected at its two bar screens, a 20 mm and a 2 mm one, in the influent water after the 20 mm screen, the effluent water, and the digested sludge. Macro- and microplastics above 500 µm were analysed individually applying ATR-FTIR, while microplastics of 10–500 µm were analysed by µFTIR imaging with automated particle recognition. Masses of plastics >500 µm were determined by weighting, while the mass of the smaller microplastics was estimated from the imaging. The total plastic load on the plant was 202.2 kg d −1, of which the two screens retained 73%. The remaining plastic mass was found in the sludge (13.6%) and the effluent (0.4%). The missing 12.7% could be caused by sampling and measuring uncertainties and potentially also fragmentation below the size detection limit of the analytical approach, or by degradation. The bar screens furthermore retained plastics smaller than the screen size, indicating that this material should be taken into account also when solely looking at smaller particles. The overall treatment efficiency of the plant was high: 99.6% considering both macro- and microplastics, and 98.8% considering only microplastics <500 µm.